Law Enforcement Against Criminal Acts with A Restorative Justice Approach in Case of Charity Box Theft - Pardi Pardi; Gunarto Gunarto; Arpangi Arpangi (Universitas Islam Sultan Agung, 2022)
The purpose of this study was to determine and analyze law enforcement against child crimes with a restorative justice approach in the case of theft of charity boxes. To find out and analyze the application of restorative justice in cases of theft of charity boxes. This study uses an empirical juridical approach, with descriptive analysis research specifications. The data used in this study is secondary data which is then analyzed qualitatively. The results of this study are Law Enforcement Against Child Crime with a Restorative Justice Approach in the Charity Box Theft case that in the application of restorative justice, it is always carried out for children who are perpetrators of criminal acts. In some cases, the restorative justice efforts can obtain an agreement by each party, so that the case is not continued to the prosecution level. The application of restorative justice is only for minor crimes, with a mediation process by deliberation. Application of Restorative justice in the Charity Box Theft Case carried out based on consensus deliberation between the victims, perpetrators, and community leaders, where the parties are asked to compromise to reach an agreement. Each individual is asked to give in and put the interests of the community above personal interests in order to maintain mutual harmony. The concept of deliberation has proven to be effective in resolving disputes in society amidst the failure of the role of the state and courts in providing justice. With the application of restorative justice, the case stops until the investigation stage or is not forwarded to court.